Ligation of the internal iliac arteries. - Arana, Julio (2015)
The study includes 45 cases of bilateral hypogastric artery ligation, 25 performed at Cayetano Heredia Hospital Lima Peru, and the remaining 20 in private practice. A historical review is done, and the hemodynamics, timing and pathways are commented. Indications and surgical procedure are presented. The mortality rate was 2% and complications were present in 57%. As a conclusion, this rgical technique must be available in every department of Obstetrics and Gynecology.